Establishing an effective internal control system for fraud prevention: a structured literature review / Nor Hafizah Abdul Rahman ... [et al.] - Abdul Rahman, Nor Hafizah; Jamaluddin, Adibah; Hamzah, Noradiva; Aziz, Khairul Azman (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA (UiTM) Shah Alam, 2019)
This study presents a structured literature review of an effective internal control system. The purpose of this study is to explore and review articles in the field of internal control effectiveness using the Guthrie, Ricceri and Dumay (2012)’s framework. The literature indicates that effective internal control can reasonably reduce business risks and prevent occurrence of fraud. This paper reports findings, based on articles on internal control effectiveness published from 2000 to 2018. The review process was conducted in five stages, (1) formulation of research objectives to determine the classifications, boundaries, and definition; (2) the selection of journals; (3) the examination of the title and abstract of selected articles; (4) pilot test and adapted classification and (5) the classification to establish a range of descriptive statistics in order to understand the patterns emerging from the reviewed articles. The finding provide a basis for several aspects of future research of internal control effectiveness in assessing business risks for prevention of fraud.